Effect of Housing Aggressions on The Agricultural Lands on The Jordanian Economic Development from the Perspective of Employees in Directorates of Agriculture - Dr. Mansour Safran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims at investigating the effects of Housing aggressions on the agricultural lands on the Jordanian economy from the perspective of the employees in directorates of agriculture in Jordan. To achieve objectives of the research, the researcher depended on the quantitative research method because of its suitability to conduct this kind of research and address the present phenomenon. For data collection, the researcher has depended on two sources, secondary data was collected from review of previous related studies, Journals, reports and books. While primary data was collected through the use of the questionnaire as the main instrument for data collection. Data collected from the respondents was analyzed using (SPSS) software, statistical package for social sciences study population consisted of all employees at different managerial levels working in directorates of agriculture in the Hashemite Kingdom of Jordan, while the study sample individuals was determined by the simple random sampling technique to be (150) male and female employees, (100) males and (50) females. Based on the results, the researcher introducing a number of suggestions and recommendations to directorates of agriculture: - Necessity for Ministry of Agriculture through its directorates in the Kingdom to employ social media in raising the awareness about the serious harms caused by aggressions on the agricultural lands. - Supporting the farmers to remain in the sector and protecting the agricultural lands. - Necessity for issuing legislations and penalties against those who practice aggressions on the agricultural lands. To better protect and preserve the agricultural lands for the benefits of all stakeholders and the Jordanian economy as a whole.